Associations between blood manganese levels and sarcopenia in adults: insights from the National Health and Nutrition Examination Survey - Xu, Bing; Chen, Zuo-xi; Zhou, Wu-jie; Su, Jia; Zhou, Qiang (Frontiers in Public Health, 2024)
Background: While increasing concerns arise about the health effects of environmental pollutants, the relationship between blood manganese (Mn) and sarcopenia has yet to be fully explored in the general population.Objective: This study aims to investigate the association between blood manganese (Mn) levels and sarcopenia in adults.In our study, we evaluated 8,135 individuals aged 18-59 years, utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2011 to 2018. We employed generalized additive model (GAM) to discern potential non-linear relationships and utilized the two-piecewise linear regression model to probe the association between blood Mn levels and sarcopenia.Results: After adjusting for potential confounders, we identified non-linear association between blood Mn levels and sarcopenia, with an inflection point at 13.45 ug/L. The effect sizes and the confidence intervals on the left and right sides of the inflection point were 1.006(0.996 to 1.048) and 1.082 (1.043 to 1.122), respectively. Subgroup analysis showed that the effect sizes of blood Mn on sarcopenia have significant differences in gender and different BMI groups.Our results showed that a reverse U-shaped curve between blood Mn levels and sarcopenia, with an identified the inflection point at blood Mn level of 13.45 ug/L.